Kaempferol and its derivatives: Biological activities and therapeutic potential - Shazia Parveen; Irshad Ul Haq Bhat; Rajeev Bhat (Asian Pacific Journal of Tropical Biomedicine, 2023)
Kaempferol, a natural plant-origin flavonoid, exhibits therapeutic anti-inflammatory, antioxidant, anticancer, antidiabetic, and neuroprotective properties. Kaempferol acts within several distinct mechanisms like apoptotic induction in cancer cells, enzymatic inhibition, signalling pathway inhibition, and downregulation in cell viability during the G2/M phase of cell division. This review summarizes the therapeutic effects of kaempferol against several health ailments. The recent progress on kaempferol obtained from fruits and vegetables as an antioxidant, anti-inflammatory, anticancer, antidiabetic, and neuroprotective agent and its mechanisms of action are also discussed. In addition, kaempferol has been reported to be present in wastes and byproducts from post-fruit and vegetable processing. Thus, a paradigm shift towards valorizing fruits and vegetable industrial wastes/byproducts to obtain bioactive kaempferol can support the circular economy pillar for generating wealth from waste and for finding a sustainable alternative source.